Exploring Feminist Pedagogy to Create an Inclusive Learning Environment: Selected Cases at the Secondary Level - Kristine A. Cerenado; Maria Ana T. Quimbo (Philippine Social Science Journal, 2022)
This study explores the application of feminist pedagogy to create an inclusive learning environment. The teaching methodology has no standardized set of characteristics, aiming to address societal issues present inside the classroom. The objectives include describing the profile of the research participants, identifying their teaching practices, examining their experienced challenges, and gathering their recommended strategies. It follows a thematic case analysis design and uses Snowball sampling to identify four teachers handling different subject areas at the secondary level. After ensuring consent, they were interviewed online using Eaton’s (2017) interview guide. Ten themes under categories of practices, challenges, and recommendations were formed. The data analysis using Creswell’s (2007) spiral design revealed that all participants are self-identified feminists and use a student-centered approach. Moreover, results have shown that they empower learners through reflection and collaboration activities. The challenges revolve around learners' responses and attitudes. Maximizing technology is a primary strategy they suggested. This article illustrates how feminist pedagogy is a new option for teachers to provide learners with a safe space to learn, free from discrimination.